TERAPI MINUMAN JAHE DAN DAUN MINT DALAM MENGURANGI MUAL MUNTAH PADA IBU HAMIL TRIMESTER I DI PUSKESMAS MARGAJAYA - Rofiasari, Linda; Yusita, Intan; Lestari, Dias Sri; Azmawa, Ajeng; Azzahra, Fatimah; Pragholapati, Andria (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2022)
The purpose of this study was to determine the description of nausea and vomiting before and after being given a decoction of ginger and mint leaves in the working area of the Margajaya Public Health Center. This study uses a quasi experiment with one group pre-test and post-test. The population in this study were pregnant women in the first trimester who experienced nausea and vomiting at the Margajaya Health Center. This study used a purposive sampling technique with a sample size of 25 people. The administration of this intervention was observed using the PUQE-24 score twice, namely before and after the intervention. Treatment with ginger and mint leaves is able to reduce the frequency of nausea and vomiting for pregnant women in the first trimester. Health workers are expected to provide counseling and counseling regarding therapy with ginger and mint leaves that can reduce the frequency of nausea and vomiting.